Efek Gastroprotektif pemberian Rimpang Kunyit (Curcuma domestica Val.) dari Ulkus Lambung yang diinduksi oleh NSAID - Nabila Salwa Raehana (Yayasan Pendidikan Medika Indonesia, 2021)
Gastric ulcers are ranked 10th in the death category, deaths that occur due to gastric ulcer disease in Indonesia reach 0.9%, which is obtained from the death rate of 8.41 per one hundred thousand people. The mechanism of gastric ulcer formation is when there is an imbalance between the defensive and aggressive factors in the gastroduodenal mucosa. The high mortality rate is caused by excessive consumption of non-steroidal anti-inflammatory drugs (NSAIDs). Curcuminoids and essential oils are the main ingredients in turmeric. Curcuminoids that can inhibit the formation of prostaglandins and suppress the activity of the cyclooxygenase enzyme. The results of the literature study show that turmeric extract can protect the gastric mucosa by increasing mucus secretion and has a vasodilator effect so that turmeric can increase the gastric mucosal defense from NSAID-induced gastric ulcers.